Registration of R.LBK1 and R.LBK2 Sorghum Germplasm with Resistance to the Sugarcane Aphid [Melanaphis sacchari (Zehntner)]. Issue 1 (27th December 2018) - Hayes, Chad M.; Armstrong, J. Scott; Limaje, Ankur; Emendack, Yves E.; Bean, Scott; Wilson, Jeff; Xin, Zhanguo
Abstract : The sorghum [ Sorghum bicolor (L.) Moench] germplasm lines R.LBK1 (Reg. No. GP‐865, PI 687244) and R.LBK2 (Reg. No. GP‐866, PI 687245) were developed and released by the USDA in Lubbock, TX, in 2017 because of their high degree of resistance to the sugarcane aphid (SCA) [ Melanaphis sachari (Zehntner) (Hempitera: Aphidae)]. Both lines were developed using the pedigree method of plant breeding and are confirmed to be restorer lines. The breeding crosses for both lines were made in Lubbock, TX, and selections were made in Lubbock and Corpus Christi, TX. Evaluation for SCA resistance was conducted in two field locations in Texas in 2016, as well as a greenhouse experiment at the USDA‐ARS laboratory in Lubbock. Both lines express strong resistance to SCA pressures at both seedling and mature plant stages. Preliminary hybrids using highly susceptible seed parents have also shown strong resistance to SCA, indicating that the resistance is dominantly expressed in F1 hybrids using these two lines. R.LBK1 and R.LBK2 are not completely immune to the SCA, but damage is greatly reduced and resistance is extremely apparent when compared to other susceptible sorghum lines and hybrids. These lines provide much needed resistance to the SCA and are suitable as germplasm in a plant breeding program or as parental lines for hybrid development.